STATE REGULATION OF LABOR MIGRATION ABROAD IN THE CONTEXT OF SOCIO-ECONOMIC DEVELOPMENT OF UKRAINE - SVYDRUK, IRENA; SYDORCHUK, ORYSTLAVA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The article is devoted to the subject analysis of tools and definition of priorities of the state regulation of labor migration of citizens of Ukraine abroad in the context of social and economic development of the state. It is determined that the state regulation of migration processes includes monitoring, development and application of information, administrative, organizational, market and social mechanisms to reduce their intensity, mitigate the negative consequences, ensure socio-economic balance in the domestic labor market. Ukraine is an active participant in the world labor market, providing the economic systems of foreign countries with more than 3 million workers annually. It is shown that the rapid development of migration processes is due to such factors as low efficiency of the socio-economic system, insufficient consistency of government in carrying out reforms. The increase in migration processes was facilitated by Ukraine's acquisition of a visa-free regime with the EU, which greatly simplified the procedures for Ukrainians to travel abroad. The positive consequences of labor migration are the reduction of tension in the labor market, increasing the welfare of households through foreign exchange earnings, the transfer of new knowledge and experience. The negative consequences of labor migration are the outflow of young people and professionals, the shortage of highly qualified labor specialists, the deteriorating demographic situation, rising consumer prices in the domestic market. The main priority of state regulation of labor migration is the management of socio-economic factors influencing the living conditions and activities of citizens, the variability of which is due to the redistribution of investment flows in the national economic system and social forms of consumption. It is shown that despite the positive dynamics in the labor market, the unemployment rate remains high, the average salary is one of the lowest in Europe, and more than 10 million people are below the poverty line. The tasks of state regulation of migration character are generalized and the corresponding measures of regulatory influence are offered. Further research is recommended to focus on the regulation of motivational factors of labor migration and the development of tools to mitigate the negative effects of migration for the development of socio-economic potential of Ukraine.
Keywords: migration processes; socio-economic system; labor market; motivation; regulatory tools